Le courtier d’assurance a son utilité : qu’on en juge ! - Dalpé, Jean (Assurances)

(untitled) (HEC Montréal, 1985)
There exists a mutual interest between the broker and the insured which becomes evident when an insurance risk is placed or at the time a loss occurs. To illustrate this relationship, the author presents a number of cases in which services rendered by the broker to the client were highly appreciable. Insureds should indeed perceive insurance not as a merchandise bought at the lowest price tendered, but rather as a service the value of which one realizes when confronted with a loss.